Association Between TNF‐α Promoter −308 A/G Polymorphism and Systemic Lupus Erythematosus Susceptibility: A Case–Control Study and Meta‐Analysis. (22nd March 2017) - Yang, Z.‐C.; Xu, F.; Tang, M.; Xiong, X.
Abstract: The tumour necrosis factor‐α (TNF‐α) promoter −308 A/G polymorphism plays an important role in the aetiology of systemic lupus erythematosus (SLE). Several studies have estimated the association between TNF‐α −308 A/G and SLE risk. However, results were inconsistent. A case–control study was carried out to explore the association between TNF‐α −308 A/G and the SLE risk in a Chinese Han population. Meta‐analysis combining present with previous studies was conducted to further explore the association. Our case–control study included 556 patients with SLE along with 570 matched healthy controls. TNF‐α −308 A allele was significantly increased in patients with SLE compared with controls (OR = 2.184, 95% CI: 1.718–2.778, P < 0.001). Genotypes AA and AG were associated with the susceptibility to SLE as compared with the GG genotype, as well as the dominant model (AA+AG versus GG), respectively. The meta‐analysis included 41 comparative studies involving 4799 patients and 6635 controls. An association between SLE and allele A was found in the overall populations (OR = 1.70, 95% CI: 1.46–1.98, P < 0.001). In addition, we discussed the correlation between this polymorphism and lupus nephritis (LN) risk, showing that allele A was significantly related to LN in the overall populations (OR = 1.80, 95% CI: 1.21–2.68, P = 0.004). The results from our case–control study and the meta‐analysis indicate that the TNF‐α −308 A allele is significantly associated with an increased risk of SLE/LN.